PPA Tele‐Savvy: Piloting an Online Intervention with Care Partners of Persons Living with Primary Progressive Aphasia. (20th December 2022) - Morhardt, Darby; Dyslin‐Kman, Deborah Nicole; Maley, Kate; Roberts, Angela C; Weintraub, Sandra
Abstract: Background: Primary Progressive Aphasia (PPA) brings unique challenges for caregiving families. Most evidence‐based interventions available to dementia caregivers do not match their needs for tailored psychosocial support. Method: This pilot study funded by the Emory University Roybal Center is an adaptation of the evidence‐based on‐line psychoeducation program (Tele‐Savvy) to address the unique challenges facing informal caregivers of those living with PPA and to help these caregivers achieve competence in their role. Using focus group data from PPA caregivers previously enrolled in Tele‐Savvy, the program curriculum was adapted to address caring for persons living with PPA. The intervention consists of seven 90‐minute weekly videoconference sessions with weekly homework, coaching and debriefing sessions. Pre/post measures look at the effects of the program on PPA knowledge, mood, caregiver burden, perceived stress, competence, quality of life and couple relationship for 9 spouse caregivers followed by a focus group 2 weeks post‐intervention to obtain additional feedback. Result: The 7‐week course was not complete by the time of abstract submission. Results will be available at the time of the conference. Conclusion: We aim to demonstrate the feasibility of offering an online PPA caregiver intervention tailored to meet their specific needs. Future research will be conducted based on what is learned from this pilot program.